Critical Conversations: Feedback as a Stimulus to Creativity in Software Design - McCall, Raymond (Human Technology, 2010)
Three decades of creating software to support design rationale showed the author how rationale processes can promote generation of novel ideas. Rationale can promote creative design by promoting critical conversations among designers and other project participants. Critical conversations intertwine ideation and evaluation, using feedback about consequences of decisions to challenge designers to devise new ideas. Such conversations take two forms. The first is discussion involving feedback from speculation about consequences of design decisions for implementation and use. The second is discussion involving feedback from actual experiences of implementation and use of the software being designed. The former is purely a process of reflective discourse, the latter a process of situated cognition involving both action and reflective discourse. Thus, the former is pure argumentation, the latter situated argumentation. Exploiting the full potential of critical conversations for creative design requires rethinking rationale methods and integrating them into software supporting implementation and use.